MULTI-PLATFORM BASED FINANCIAL STATEMENT REPORT REPOSITORY SYSTEM AT UPT.PTPH NORTH SUMATRA - Muhammad Rizky Dermawan; Samsudin Samsudin (STMIK Royal, 2022)
Abstract: The role of information technology and information systems are two parts that cannot be separated. Both of them developed on the response of human urgency, which then has quite crucial influence and implications in this era. The development of both is fast and varied, following the aspect of increasing human need for information quickly and accurately. One example of its development in this millennial era is the development of data processing tools in the form of a repository system. The repository is a storage-based service that offers digital materials in various formats managed by certain parties to its users. UPT.PTPH North Sumatra Province is a government agency engaged in the plant and horticulture sector that does not yet have a computerized information system. To obtain related information, workers or staff must manually search for the desired data. The prototyping model used in the design proved to be adaptive in dealing with change. The results of the study reveal that a multi-platform-based financial statement repository system in the form of websites and Android applications can speed up the report processing process, provide valid financial data and a more transparent and structured data management process. Keywords: data management; information system; information technology; prototyping model; repository. Abstrak: Peran teknologi informasi dan sistem informasi merupakan dua bagian yang tidak dapat dipisahkan. Keduanya berkembang atas respon urgensi manusia, yang kemudian memiliki pengaruh dan implikasi yang cukup krusial pada zaman ini. Perkembangan keduanya yang cepat dan variatif, mengikuti dari aspek peningkatan kebutuhan manusia terhadap informasi secara cepat dan akurat. Salah satu contoh dari perkembangannya pada zaman millenial ini adalah berkembangnya alat bantu pengolahan data berupa sistem repository. Repository adalah sebuah fasilitas storage-based service yang menawarkan bahan digital dalam berbagai format yang dikelola oleh pihak tertentu kepada kalangan penggunanya. UPT.PTPH Provinsi Sumatera Utara adalah instansi pemerintah yang bergerak di sektor tanaman dan hortikultura yang belum memiliki sistem informasi terkomputerisasi. Untuk mendapatkan informasi terkait, para pekerja ataupun staff harus secara manual mencari data yang diinginkan. Prototyping model yang digunakan dalam perancangan terbukti adaptif dalam menangani perubahan. Hasil penelitian mengungkap bahwa sistem repository financial statement berbasis multi platform berupa website dan aplikasi andoid dapat mempercepat proses pengerjaan laporan, memberikan data keuangan yang valid serta proses pengelolaan data yang lebih transparan dan terstruktur. Kata Kunci: model prototyping; pengelolaan data; repository; sistem informasi; teknologi informasi.